The process of resource bricolage and organizational improvisation in information technology innovation: a case study of BDZX in China - Hu, Haibo; Lu, Haitao; Huang, Tao; Wei, William Xiaojun; Mao, Chunbing; Thomson, Stanley Bruce (My University, 2022)
Research has shown there is a connection between bricolage and improvization, but discussion about their dynamic relationship in fixed situations is limited. In the context of information technology (IT) innovation, three aspects of corporate strategic actions are analyzed in this article by the exploratory single case study of BDZX in China. The following results were found: (1) IT innovation has experienced a transformation from component to architectural innovation, triggering corporate strategic actions; (2) Resource bricolage in IT innovation process is divided into combined resources and resetting resources, and organizational improvization in IT innovation process is divided into integration capabilities and development capabilities; (3) In IT innovation, the impact of resource bricolage on companies is gradually increasing, while the impact of organizational improvization on companies is gradually decreasing.
Keywords: IT innovation; resource bricolage; organizational improvization; turbulent environments; exploratory case study